2017
DOI: 10.1002/ird.2102
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctive use of saline and non-saline water in an irrigation district of the Yellow River Basin

Abstract: In the Hetao Irrigation District (HID), reduction of the diverted Yellow River water for agriculture makes partial replacement of fresh water for irrigation by shallow saline groundwater a possible way to alleviate the shortage of freshwater resources. In this study, a SWAP‐WOFOST agro‐hydrological model was calibrated and validated, and then applied in a distributed manner to estimate crop yield, water productivity (WP) of spring wheat, spring maize, and sunflower, and soil salinity with conjunctive use of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…As one of the most widely consumed cereals, maize is classified as a mild salt-tolerant crop [24], whose planting area accounts for more than 30% of the total tillage in the HID [1]. There are many studies about the influence of irrigation water salinity on maize plant height, leaf area, dry matter, yield characteristics, and water use efficiency [10,12,13,17,18,23,[25][26][27], while few studies have focused on the impacts of irrigation water salinity on maize emergence and grain quality.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most widely consumed cereals, maize is classified as a mild salt-tolerant crop [24], whose planting area accounts for more than 30% of the total tillage in the HID [1]. There are many studies about the influence of irrigation water salinity on maize plant height, leaf area, dry matter, yield characteristics, and water use efficiency [10,12,13,17,18,23,[25][26][27], while few studies have focused on the impacts of irrigation water salinity on maize emergence and grain quality.…”
Section: Introductionmentioning
confidence: 99%
“…A huge potential of water available in upper aquifers of NCP is characterized by brackish water at around 4.7 dS m −1 [54]. Utilization of this water for winter crops is important to cope up with the current tight water situation [23,[55][56][57]. The NCP illustrates the challenges facing China as it deals with increased water demands and severe ground depletion [41].…”
Section: Discussionmentioning
confidence: 99%
“…The successful amalgamation of alternate irrigation water in this region offers great potential of saline water resources. Irrigation with SS treatment produced the lowest crop yield compared to other treatments [3,55]. If fresh water were available during initial crop stages for the better tillering of winter wheat, the saline water irrigation can be more effectively applied at other crop development stages.…”
Section: Discussionmentioning
confidence: 99%
“…Xue at al. reported that using brackish and fresh water together was an important way to reduce soil salinity [19]. For example, Hassanli noticed that there was no significant difference between initial and final salt concentrations in the soil profile under alternate irrigation [20].…”
Section: Introductionmentioning
confidence: 99%